Annual Premium Calculation On Single Life Insurance using Gompertz Mortality Assumptions - Michelle Novia; Fauziah Nur Fahirah Sudding (Journal of Actuarial, Finance, and Risk Management, 2023)
Premium calculation is one of the important aspects to insurance companies. Given the importance of premiums in insurance contracts for insurance companies, determining the price of the premium must also be appropriate. Careless determination of the premium price can cause the insurance company to fail to bear the risk that the company has. There are several ways to determine premium payments. In this research the premium calculation will be computed using Gompertz mortality assumptions which will be applied to the annual premium calculation of whole life single life insurance of man and woman. The benefit assumed, interest rate, Insurer age, Gompertz parameter and several actuarial notations such as life annuity-due and net single premium is needed in the premium calculation using Gompertz mortality assumptions. This research uses the data of Indonesian Mortality table (TMI IV) and the Linear Least Squares (LLS) method to find the Gompertz parameter which then be used to find the life annuity-due that will be needed to compute the premium calculation of Gompertz assumptions. Based on the calculation performed in this research, the value of the premium using Gompertz assumptions is influenced by parameters on the Gompertz assumptions, the interest rate used, and the Insured age.